(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
The importance of accounting is due to its close relationship with the money that constitutes the very nerve of economic life, and accounting as the appropriate means to manage and spend it rationally, hence the place privilege occupied by the accounting profession among the other professions, because of the multiplicity of its functions and powers. As a result, the accountant enjoys wide powers and holds the economic keys of the company or the company, and the accountant is responsible for his professional and personal mistakes, as well as for his illegal acts, which is the responsibility of the accountant. he committed a proven error may go beyond disciplinary liability to that of contract or delict . Keywords: Civil Liability, Disciplinary Liability, Accounting Board, Accounting Experience .Certified Accountant.